Dosimetric Deviations of Bragg-Peak Position Shifts in Uniform Magnetic Fields for Magnetic Resonance Imaging-Guiding Proton Radiotherapy: A Monte Carlo Study - Wang, Xiaowa; Pan, Hailun; Cheng, Qinqin; Wang, Xufei; Xu, Wenzhen (Frontiers in Public Health, 2021)
Abstract Objective: We investigate dosimetric deviations of proton Bragg-peak position shifts caused by proton spiral tracks in an ideal uniform field of magnetic resonance (MRI) imaging-guided proton radiotherapy (MRI-IGPRT) in a Monte Carlo study. Methods: Use the FLUKA Monte-Carlo (MC) code to simulate the spiral tracks of protons penetrating in water with initial energies of 70-270 MeV under the influence of field strength of 0.0-3.0 Tesla of commercial MRI systems. We analyze the Bragg-peak positions of spiral proton tracks by a lateral shift (marked as: ) perpendicularly to the field and a penetration-depth shift (marked as: ) along the beam path. We compare MC simulated values of and with calculated values of an analytical model. Besides the shifts of Bragg-peak positions, the shapes of 2D/3D dose distribution of proton spots at the depth of Bragg-Peak become asymmetric. We investigate the asymmetric spot-shape by the ratio of Gaussian-fit values between longitudinal and transverse major axes. We also evaluated the skewness of asymmetry at various dose levels by the radius ratios of circumscribed and inscribed circles by fitting a semi-ellipse circle of 2D distribution at each dose level. Results: The maximum of deflection is 2.82cm while the maximum of shorten is 0.44cm for protons with 270 MeV under a magnetic field of 3.0 Tesla. The trends of and from MC simulations agree with calculated values of analytical model. We can apply the reverse equation of the analytical model to find the proper field strength of magnet and the initial energy of proton for desired values of and ; it allows placing the locations of Bragg-peak to achieve a desired dose. The asymmetry of 2D/3D dose distribution under the influence of magnetic field increases as increased proton energy. The skewness of asymmetry for a proton energy at various dose levels increases as increased radius; i.e. a lower dose level. Conclusions: The trend of the spiral proton tracks under a uniform magnetic field obtained in this study by using either MC simulation or the analytical model can provide optimized and desired doses of proton beam in the clinical application of MRI-IGPRT. I-IGPRT.